Wave Load Mitigation by Perforation of Monopiles - Jacob Andersen; Rune Abrahamsen; Thomas Lykke Andersen; Morten Thøtt Andersen; Torben Ladegaard Baun; Jesper Lykkegaard Neubauer (Journal of Marine Science and Engineering, 2020)
The design of large diameter monopiles (8–10 m) at intermediate to deep waters is largely driven by the fatigue limit state and mainly due to wave loads. The scope of the present paper is to assess the mitigation of wave loads on a monopile by perforation of the shell. The perforation design consists of elliptical holes in the vicinity of the splash zone. Wave loads are estimated for both regular and irregular waves through physical model tests in a wave flume. The test matrix includes waves with Keulegan–Carpenter ( <semantics> K C </semantics> ) numbers in the range 0.25 to 10 and covers both fatigue and ultimate limit states. Load reductions in the order of 6%–20% are found for <semantics> K C </semantics> numbers above 1.5. Significantly higher load reductions are found for <semantics> K C </semantics> numbers less than 1.5 and thus the potential to reduce fatigue wave loads has been demonstrated.